HBR guide to persuasive presentations - Duarte, Nancy (Boston, Mass. : Harvard Business Review Press, 2012)
Terrified of speaking in front of a group? Or simply looking to polish your skills? No matter where you are on the spectrum, this guide will give you the confidence and the tools you need to get results. Learn how to wIn over tough crows, organize a coherent narrative, create powerful messages and visuals, connect with and engage your audience, show people why your ideas matter to them, and strike the right tone, in any situation.
Understand the audience's power -- Segment the audience -- Present clearly and concisely to senior executives -- Get to know your audience -- Define how you'll change the audience -- Find common ground -- Define your big idea -- Generate content to support the big idea -- Anticipate resistance -- Amplify your message through contrast -- Build an effective call to action -- Choose your best ideas -- Organize your thoughts -- Balance analytical and emotional appeal -- Lose the jargon -- Craft sound bites -- Apply storytelling principles -- Create a solid structure -- Craft the beginning -- Develop the middle -- Make the ending powerful -- Add emotional texture -- Use metaphors as your glue -- Create something they'll always remember -- Choose the right vehicle for your message -- Make the most of slide software -- Determine the right length for your presentation -- Persuade beyond the stage -- Share the stage -- Think like a designer -- Create slides people can "get" in three seconds -- Choose the right type of slide -- Storyboard one idea per slide -- Avoid visual clichés -- Arrange slide elements with care -- Clarify the data -- Turn words into diagrams -- Use the right number of slides -- Know when to animate -- Rehearse your material well -- Know the venue and schedule -- Anticipate technology glitches -- Manage your stage fright -- Set the right tone for your talk -- Be yourself -- Communicate with your body -- Communicate with your voice -- Make your stories come to life -- Work effectively with your interpreter -- Get the most out of your q&a -- Build trust with a remote audience -- Keep remote listeners interested -- Keep your remote presentation running smoothly -- Build relationships through social media -- Spread your ideas with social media -- Gauge whether you've connected with people -- Follow up after your talk.
Includes index.
Description based on print version record.
Keywords: Business presentations; Persuasion (Psychology); Business presentations; Persuasion (Psychology); BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books